Serotonergic chemosensory neurons modify the C. elegans immune response by regulating G-protein signaling in epithelial cells. - Alexandra Anderson; Henry Laurenson-Schafer; Frederick A Partridge; Jonathan Hodgkin; Rachel McMullan (PLoS Pathogens)
The nervous and immune systems influence each other, allowing animals to rapidly protect themselves from changes in their internal and external environment. However, the complex nature of these systems in mammals makes it difficult to determine how neuronal signaling influences the immune response. Here we show that serotonin, synthesized in Caenorhabditis elegans chemosensory neurons, modulates the immune response. Serotonin released from these cells acts, directly or indirectly, to regulate G-protein signaling in epithelial cells. Signaling in these cells is required for the immune response to infection by the natural pathogen Microbacterium nematophilum. Here we show that serotonin signaling suppresses the innate immune response and limits the rate of pathogen clearance. We show that C. elegans uses classical neurotransmitters to alter the immune response. Serotonin released from sensory neurons may function to modify the immune system in response to changes in the animal's external environment such as the availability, or quality, of food.